Fuzzy Cooperative Games Cooperation with Vague Expectations - Mareš, Milan (Studies in Fuzziness and Soft Computing, 2001)
The book deals with the mathematical model of coalitional cooperation based on vague knowledge of its expected outcomes. This reality is described by the model of coalitional game (with or without transferable utility) in which the expected pay-offs are represented by fuzzy quantities or by fuzzy sets of real-valued vectors. This approach to the fuzziness in the bargaining is new and completes the existing literature on this topic by alternative views. The presentation does not demand deeper than elementary knowledge of linear algebra and some related topics. The book can be used as an introduction to the subject presenting basic concepts and results